Motivasi Belajar Dalam Al Quran At Taubah Ayat 122 Studi Ilmu Pendidikan Islam - Izzan, Ahmad; Mubarok, Muhammad Husni (STAI Al-Musaddadiyah Garut, 2025)
Learning is a process of activity to change the behavior of students, many factors influence it. Among them are motivational factors that function as efforts in achieving achievements. Student learning motivation greatly influences student learning outcomes. The process of teaching and learning and fostering motivation in Islam cannot be separated from the main source of teachings, namely the Qur'an. In the Qur'an, there are many expressions that show encouragement to every Muslim to learn. As in the Qur'an, Surah At-Taubah Verse 122. This verse contains meanings related to learning motivation. This study aims to describe the learning motivation contained in the Qur'an, Surah At-Taubah Verse 122, Study of Islamic Education. This research is a type of library research, namely by conducting research on the results of the interpretation of the interpreters of the Al-Qur'an Surah At-Taubah Verse 122 and written sources or other literature on learning motivation put forward by experts or scholars. The research method used is a qualitative method by focusing on the analysis of the content of the Al-Qur'an Surah At-Taubah Verse 122 and the contents of the text of books related to the title being studied. The results of this study indicate that the learning motivation contained in the Al-Qur'an Surah At-Taubah Verse 122 explains that jihad is not only on the battlefield but also deepening knowledge is part of jihad itself. As for learning motivation in the Al-Qur'an Surah. At-Taubah Verse 122 Study of Islamic Education Science states that Allah SWT motivates humans to deepen religious knowledge or study, in fact Allah SWT gives the same reward to people who fight in the way of Allah and people who seek knowledge. Allah SWT demands that His servants strive for jihad by taking up weapons and deepening their knowledge and understanding it. Thus, it is clear that the meaning of the Al-Qur'an Surah At-Taubah Verse 122 can be a motivation for Muslims to be more active and serious in studying, especially in studying religious knowledge. Keywords: Learning Motivation, Islamic Education, Learning Achievement